The art of combining neuroanatomy and microsurgical skills in modern neurosurgery - Ahumada-Vizcaino, Juan Carlos; Wuo-Silva, Raphael; Hernández, Manuel Moreno; Chaddad-Neto, Feres (Frontiers in Neurology, 2023)
Neurosurgical training outside the operating room has become a priority for all neurosurgeons around the world. The exponential increase in the number of publications on training in neurosurgery reflects changes in the environment that future neurosurgeons are expected to work in. In modern practice, patients and medicolegal experts demand objective measures of competence and proficiency in the growing list of techniques available to treat complex neurosurgical conditions. It is important to ensure the myriad of training models available lead to tangible improvements in the operating room. While neuroanatomy textbooks and atlases are continually revised to teach the aspiring surgeon anatomy with a three-dimensional perspective, developing technical skills are integral to the pursuit of excellence in neurosurgery. Parapharsing William Osler, one of the fathers of neurosurgical training, without anatomical knowledge we are lost, but without the experience and skills from practice our journey is yet to begin. It is important to constantly aspire beyond competence to mastery, as we aim to deliver good outcomes for patients in an era of declining case volumes. In this article, we discuss, based on the literature, the most commonly used training models and how they are integrated into the treatment of some surgical brain conditions.